Burek : A Culinary Metaphor - Mlekuž, Jernej (Book collections on Project MUSE., 2015)
"'As Simple as Burek' is a saying current among young people in Slovenia. But in his book, Jernej Mlekuž holds just the opposite. The burek--a pie made of pastry dough filled with various fillings, well-known in the Balkans, Turkey (bürek), and also in the Near East by other names--whether on the plate or as a cultural artifact, is in fact not that simple. After a brief stroll though its innocent history, before parasitical ideologies had attached themselves to the burek and poisoned its discourses, Mlekuž focuses on the present. In Slovenia, the burek has become a loaded metaphor for the Balkans and immigrants from the republics of the former Socialist Federal Republic of Yugoslavia. Without the burek it would be equally difficult to consider the jargon of Slovenian youth, the imagined world of Slovenian chauvinism and the rhetorical arsenal of advertising agents when promoting healthy foods. In this analysis therefore, the burek is always what Mlekuž calls the metaburek. It is greasy, Balkan, Slovene, not-Slovene, the greatest, eastern, the best, shit, oriental, unhealthy, plebian, Yugoslav, junk, a cherub (burek spelled backwards is kerub, the Slovene word for cherub). And this metaburek, which is the protagonist of this book, is never a completely pure, innocent, unconditioned burek. It is much more than just a burek. And a word of warning: after consuming this text, the burek will never be the same"--Provided by pubolisher.